La WOL dans les Ardennes et les rapports géographie – nazisme au sein du IIIe Reich - Philippe Moyen (M@ppemonde)
The 1940 defeat by Germany led to profound changes in the national territory. In addition to the establishment of a demarcation line between occupied France and the free zone, the Führer’s line separates France from territories located east of a line between the Somme river entrance and the Swiss border. Most of the territory of the Ardennes fell within this forbidden zone. The occupation was reflected, among other things, in the implementation of a policy of agrarian rationalization under the leadership of WOL III, a regional agricultural management of the Nazi company Ostland. The constitution of a National Socialist agrarian system offers a privileged field to study the relations between geography and political power within the Third Reich.